Gender, health and field encounters in Southern Africa: methodological innovation on data collection methods for evaluating international development programmes - Carvalho, X. (1st Societal Health Conference – “Societal health in the Post-covid-19 future”, 2022)
Social inequalities accessing health are a key issue in understanding how health systems are designed, evaluated and improved (Beckfield, Olafsdottir and Bakhtiari, 2013; Llop-Gironés et al., 2019; O’Laughlin, 2010). My focus is on the assessment of the international development programmes in Southern Africa, particularly in Mozambique, using a mix methodology and looking at the Maternal and Child Survival Program (MCSP) implemented by the United States Agency for International Development (USAID) from 2016 to 2018 (COWI, USAID, MISAU, 2019a, 2019b). Health research in Southern Africa has a high rate of dependence especially regarding external donor funding, based upon top-down policies that do not reflect local and regional socio-economic realities (Llop-Gironés et al., 2019; IHME, 2016). In a general overview, the population has low access to health care services, especially in rural areas and in the North provinces of the country, due to low education levels, low socioeconomic status, and gender inequality (Llop-Gironés et al, 2018, 2021; World Health Organization, 2015; IHME, 2016). To understand how health is perceived and used by Mozambicans, I draw critically on the qualitative endline survey done to evaluate the MCSP in Mozambique (COWI, USAID, MISAU, 2019a, 2019b). When looking in a global perspective, Mozambique has one of the highest maternal and infant mortality rates (INE, 2015), and USAID, as an external donor, as implemented the MCSP, in May 2016, in partnership with MISAU (Minister of Health of Mozambique), in Sofala and Nampula provinces. The MCSP aimed at developing and supporting high-impact, sustainable reproductive, maternal, new-born and child health (RMNCH) interventions, focusing on increasing access and strengthen the local health system, contributing for reducing one of the major challenges in the country: distances of accessing health facilities. A four-dimension analyses of accessing health facilities in developing countries underlines geographic accessibility, availability, financial accessibility, and acceptability (Levesque et al., 2013; Dos Anjos and Cabral, 2016) as key to understand quality care. The first dimension is the one that has higher impact on developing inclusive public health policies due to the physical distance or travel time that population spends to reach health care in Mozambique, underlined by social inequalities (COWI, USAID, MISAU, 2019a, 2019b). To evaluate the impact of the MCSP interventions in the country, in November and December of 2018, an endline survey divided into two dimensions (i.e., female narratives and male engagement plus couples’ communication) was conducted in the field using a qualitative approach, within a mix methodology frame, applying in-depth Interviews and focus groups techniques to collect data. Besides the donor tools’ prête à porter, direct observation (Hagberg and Ouattara, 2012; Fix at al., 2022; Bernard, 2006; Bourgois, 1990; Adam, 1994) was introduced to reinforce and explore in-depth the subaltern voices of women and men (Spivak, 1988; Lawson, 2007; Hall, 1992; Nkwi, 2006) and the way they are narrow down in the donor evaluations, impacting negatively on health systems improvement.